2014
DOI: 10.1186/s40623-014-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

Origin and transport of pore fluids in the Nankai accretionary prism inferred from chemical and isotopic compositions of pore water at cold seep sites off Kumano

Abstract: We used push corers during manned submersible dives to obtain sediment samples of up to 30 cm from the subseafloor at the Oomine Ridge. The concentrations of B in pore water extracted from the sediment samples from cold seep sites were higher than could be explained by organic matter decomposition, suggesting that the seepage fluid at the site was influenced by B derived from smectite-illite alteration, which occurs between 50°C and 160°C. Although the negative δ 18 O H2O and δD H2O values of the pore fluids c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…6K949, May 6th, 2006). The detailed sediment core sample and site information has been described previously 15,42,43 . Our previous geochemical and 16S rRNA gene analysis indicated that the occurrence of anaerobic oxidation of methane (AOM) reactions mediated by archaeal anaerobic methanotrophs (ANMEs) in the sediment 15,42 .…”
Section: Methodsmentioning
confidence: 99%
“…6K949, May 6th, 2006). The detailed sediment core sample and site information has been described previously 15,42,43 . Our previous geochemical and 16S rRNA gene analysis indicated that the occurrence of anaerobic oxidation of methane (AOM) reactions mediated by archaeal anaerobic methanotrophs (ANMEs) in the sediment 15,42 .…”
Section: Methodsmentioning
confidence: 99%
“…The upward migration of fluids, including methane, to the Kumano forearc basin succession is constrained by the structural architecture of the underlying accretionary prism complex. Previous studies have proposed several structural models (Morita et al, 2004;Toki et al, 2014;Nishio et al, 2015). Tsuji et al (2015) and Jia et al (2016) described an out-ofsequence thrust fault in the accretionary prism which was tentatively identified as the main pathway for gas migration into the forearc basin succession; fluid migration routes across the basal unconformity could include fractures assocated with past movement on the thrust, which is currently inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuji et al (2015) and Jia et al (2016) described an out-ofsequence thrust fault in the accretionary prism which was tentatively identified as the main pathway for gas migration into the forearc basin succession; fluid migration routes across the basal unconformity could include fractures assocated with past movement on the thrust, which is currently inactive. Toki et al (2013Toki et al ( , 2014 discussed the origin of fluids derived from clay mineral dehydration reactions in the 150-160 °C temperature zone in the accretionary prism, corresponding to depths of 4 km bsf or more. Nishio et al (2015) reported evidence from mud volcanoes of fluids derived from depths of more than 20 km.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature profile is disturbed if there is advective fluid flow in the Kumano forearc sediments (e.g., Toki et al 2014;Yamano et al 2014). Although we cannot exclude this possibility, it is not likely for negative thermal anomalies because decreasing the temperature would require an input of shallower source fluid in the downward direction, which is difficult under the lithological condition around this site.…”
Section: Possible Causes For Thermal Excursionsmentioning
confidence: 99%